2022
DOI: 10.1159/000528611
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Recovery 12 Months after Non-Severe and Severe COVID-19: The Prospective Swiss COVID-19 Lung Study

Abstract: <b><i>Background:</i></b> Lung function impairment persists in some patients for months after acute coronavirus disease 2019 (COVID-19). Long-term lung function, radiological features, and their association remain to be clarified. Objectives: We aimed to prospectively investigate lung function and radiological abnormalities over 12 months after severe and non-severe COVID-19. <b><i>Methods:</i></b> 584 patients were included in the Swiss COVID-19 lung study. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Severe acute COVID-19 is associated with more breathlessness and a lower DLCO, %, value in post-COVID-19 conditions. 73,92 Perhaps, the two different causes of restrictive lung disease in post-COVID-19 conditions explain why we found different proteins associated with FVC, %, than with DLCO, %; the dysregulation of different proteins may cause respiratory muscle weakness versus the interstitial lung disease in post-COVID-19 conditions.…”
Section: Forced Vital Capacity and Post-covid-19mentioning
confidence: 83%
“…Severe acute COVID-19 is associated with more breathlessness and a lower DLCO, %, value in post-COVID-19 conditions. 73,92 Perhaps, the two different causes of restrictive lung disease in post-COVID-19 conditions explain why we found different proteins associated with FVC, %, than with DLCO, %; the dysregulation of different proteins may cause respiratory muscle weakness versus the interstitial lung disease in post-COVID-19 conditions.…”
Section: Forced Vital Capacity and Post-covid-19mentioning
confidence: 83%
“…A total of 2517 studies were identified, of which 43 met the inclusion (N = 8858 patients) ( Figure 1 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. The majority of studies were from China (14 studies [ 51 , 58 , 59 , 60 , 61 , 64 , 65 , …”
Section: Resultsmentioning
confidence: 99%
“…The median age of the patients was 60.3 years (57–63), with 61.5% being males and 37.8% being current/former smokers. Thirty-nine studies [ 47 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 65 , 66 , 67 , 68 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ] reported outcomes stratified by disease severity; 17 for non-severe disease, 31 for severe disease, and 7 for mixed disease severity ( Table 1 ). The most common comorbidities were hypertension (35.8%), cardiovascular disease, (28%), and obesity (24.9%) ( Supplemental Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Respiratory failure is one of the main causes of death in severe COVID-19 patients ( Ohuabunwa et al., 2022 ). Meanwhile, studies found that patients with severe COVID-19 had severe respiratory symptoms during hospitalization, including lower oxygen saturation, and diminished lung function compared to those after non-severe COVID-19 ( Bieńkowski et al., 2022 ; Lenoir et al., 2022 ). Compared to patients with non-severe coronavirus pneumonia, lower oxygen saturation and lung function in the first year in patients with severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%